Expression and clinical significance of serum cystatin C in patients with hypertension and coronary heart disease. Issue 22 (29th May 2020) - Zhao, Miaohui; Che, Qingqing; Zhang, Yandan; Qian, Xingjun; Huang, Tong
Abstract : Abstract: The aim of this study is to explore the potential association between cystatin C (Cys-c) and coronary heart disease (CHD) in hypertensive patients. In this study, circulating levels of Cys-c in 62 essential hypertension (EH) patients, 147 hypertension with coronary heart disease (EH + CHD) patients, and 60 healthy volunteers were investigated using immunoturbidimetry. Then, we analyzed the correlations between Cys-C and other clinical parameters. Serum Cys-C level was significantly higher in the EH and EH + CHD groups than in the control group, and higher in the EH + CHD group than in the EH group. Receiver operating characteristic curve (ROC) analysis showed that the diagnostic value of Cys-C for patients with hypertension combined CHD was 0.871(95% CI: 0.818–0.913). Serum Cys-C level was significantly higher in the double-vessel disease group and multi-vessel disease group than in the single-vessel disease group, and higher in the multi-vessel disease group than in the double-vessel disease group. Urinary albumin and CRP correlated positively with Cys-C, and HDL correlated negatively with Cys-C. Cys-C was an independent risk factor for CHD in hypertensive patients. Our results suggested that circulating Cys-C levels was up-regulated in patients with hypertension and CHD, and had correlation with the severity of coronary artery disease. As one of the important risk factors for CHD, Cys-C can predict the occurrence of CHD in patients with hypertension.